2015
DOI: 10.1159/000437222
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Confocal Microscopy Features of Focal Dermal Mucinosis Differ from Those Described for Basal Cell Carcinoma: Report of Two Cases

Abstract: The purpose of this study was to describe the reflectance confocal microscopy (RCM) features of focal dermal mucinosis (FDM). The entity clinically and dermatoscopically mimics other diagnostic entities, most notably nonpigmented basal cell carcinoma. We describe two cases that highlight the dermatoscopic, RCM and histopathological attributes of FDM. RCM features such as dermal foci of dense collagen bundles oriented in the same direction, foci of haphazardly oriented thin collagen fibers separated by dark str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Although the number of patients in this study was small, and more studies are needed to standardize patterns on RCM in dermal mucinoses, RCM may be a promising method for diagnosis. 43…”
Section: Histologymentioning
confidence: 99%
“…Although the number of patients in this study was small, and more studies are needed to standardize patterns on RCM in dermal mucinoses, RCM may be a promising method for diagnosis. 43…”
Section: Histologymentioning
confidence: 99%
“…Paget cells contain intracytoplasmic mucin [ 9 12 ], a mixture of acid mucopolysaccharides. Fraga-Braghiroli et al have shown that mucin located areas in dermal mucinosis were seen as darker areas on RCM [ 13 ]. Likewise, Ulrich et al have shown that the peritumoral cleft-like spaces seen in BCC on histopathology exist in vivo, and correspond to the peritumoral mucin deposition which also demonstrates that mucin appear dark on RCM [ 14 ].…”
Section: Discussionmentioning
confidence: 99%